Export marketing: Strategies for success - Arora, Neha (Sublime, 2015)
Export marketing is a systematic process of developing and distributing goods and services in overseas markets. The export marketing manager needs to undertake various marketing activities such as marketing research, product design , branding packaging pricing , promotion etc to undertake the various marketing activities the export marketing managers should collect the right information from the right source analyse it properly and then take systematic export marketing decision. Many business firms who entered in to international markets could not do well and perished simply because their products were not up to international standards and firms could not match marketing needs. this books describes the steps necessary to achieve success in export marketing